2013
DOI: 10.1038/hdy.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Antennapedia is involved in the development of thoracic legs and segmentation in the silkworm, Bombyx mori

Abstract: Homeotic genes, which are associated closely with body patterning of various species, specify segment identity. The Wedge eye-spot (Wes) is a new homeotic mutant located on the sixth linkage group. Homozygous Wes/Wes embryos are lethal and display a pair of antenna-like appendages under the mouthparts as well as fused thoracic segments. These mutants also exhibit a narrower eye-spot at the larval stage compared with the wild type. By positional cloning, we identified the candidate gene of the Wes locus, Bombyx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
(37 reference statements)
3
18
0
1
Order By: Relevance
“…In Drosophila , the Antp , Ubx and Abd-B genes were involved in development of the thoracic leg, wing and gonad respectively, which corresponds to their functional domain 34 35 36 . Similarly, our previous study suggested that the Antp gene is required for the organization of thoracic legs in B. mori 37 . These results suggested that multiple mutation phenotypes of the ap mutant might be related to the expression of the corresponding Hox gene, and provide clues for studying the mechanism underlying Hox gene expression.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In Drosophila , the Antp , Ubx and Abd-B genes were involved in development of the thoracic leg, wing and gonad respectively, which corresponds to their functional domain 34 35 36 . Similarly, our previous study suggested that the Antp gene is required for the organization of thoracic legs in B. mori 37 . These results suggested that multiple mutation phenotypes of the ap mutant might be related to the expression of the corresponding Hox gene, and provide clues for studying the mechanism underlying Hox gene expression.…”
Section: Discussionsupporting
confidence: 66%
“…Eggs from non-mated females were dissected and rinsed with double-distilled water. For scanning electron microscopic observation, the eggs were processed as previously described 37 and were coated with gold before observation under a scanning electron microscope (S-3000N, Hitachi, Tokyo, Japan). For artificial parthenogenesis, the newly dissected eggs were treated according to the following steps: 1) incubated at 25 °C for 12 h; 2) placed in the hot water at 46 °C for 18 min; 3) taken out of the water and incubated at 25 °C for 10 min; 4) transferred to 16 °C for 3 days; 5) treated with hydrochloric acid (sp.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly marked example is provided by the Antp gain-of-function mutations in Drosophila melanogaster, which transform the antennae into second thoracic legs (Kaufman et al, 1990). Antp loss-of-function mutation in silkworm produced the fused thorax and defects in limb development (Chen et al, 2013a). The Hox gene Ubx is normally expressed in a complex pattern in the posterior thoracic and anterior abdominal segments of insects, where it has multiple roles in modifying specific morphological differences between the mid-legs (T2) and meta-legs (T3) on the thorax, including appendage size, shape and function (Averof and Patel, 1997;Akam, 1998;Roch and Akam, 2000;Tomoyasu et al, 2005), and inhibit the development of abdominal prolegs via repressing the Distal-less (Dll) expression (Gebelein et al, 2002;Ronshaugen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although insects expressed abd-A in a similar pattern from the posterior compartment of the first abdominal segment to the remaining abdominal segments (Kelsh et al, 1994;Shippy et al, 1998), there is considerable diversity in the prolegs distribution on the abd-A expressed segments among various insects, with a wide range of variation in both segmental arrangement and number. In Diptera Drosophila (Vachon et al, 1992) and Coleoptera Tribolium (Lewis et al, 2000), abd-A suppressed leg development by inhibiting expression of the gene Dll leading to the deficiency of abdominal limbs in larvae, however, abd-A promotes the development of prolegs in silkworm (Chen et al, 2013a). The Abd-B gene is expressed in the last few segments of the abdomen and is required for proleg suppression in these segments (Tomita and Kikuchi, 2009;Xiang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Armadillo is expressed in the actual eyespot centers in late larval stages (Connahs et al 2019), as is Antennapedia ( Antp ; BANY.1.2.g02571), a hox gene (Saenko et al 2011; Tong et al 2014; Özsu and Monteiro 2017). Antp is also involved in the differentiation of the thoracic limbs in Bombyx moths (Chen et al 2013). Ultrabithorax ( Ubx ; BANY.1.2.g02579) is another hox gene that gives insect hindwings a different identity from forewings (Weatherbee et al 1999; Tong et al 2014).…”
Section: Discussionmentioning
confidence: 99%